Corporate tax avoidance and firm performance: the moderating role of ownership concentration and board independence - Muhammad Shaukat Malik; Muhammad Irfan; Samavia Munir (Cogent Business & Management, 2025)
Corporate tax avoidance is planning strategies to use tax law and accounting standards to reduce the amount of tax payable to government and that is expected to improve firm performance. Nevertheless, agency theory explains the opportunistic behavior of manager who can reduce the tax obligation by using various complex transactions to fulfill their personal interest. Therefore, the present study explores the relationship between corporate tax avoidance and firm performance. It also identifies the moderating role of ownership concentration and board independence in this relationship. Until now there exists no empirical evidences in the context of South Asian Association for Regional Cooperation (SAARC) economies. To address this gap, the current study explores the empirical relationship by using the sample from the 91 banking firms of four SAARC countries namely Pakistan, India, Bangladesh and Sri Lanka during the period from 2010 to 2021. Moreover, this is a first study that provides interesting comparison among these countries by using 264 observations from Pakistan, 312 observations from India, 384 observations from Bangladesh and 132 observations from Sri Lanka by using pooled OLS, fixed and random effect regression techniques. Empirical findings confirm that, for Pakistan, Bangladesh, and Sri Lanka, corporate tax avoidance doesn’t play significant role in improving firm performance, however, India confirms the positive relationship. The results indicate that ownership concentration and board independence do not moderate the relationship for banking firms in Pakistan, India, and Sri Lanka, whereas in Indian banking firms, ownership concentration positively moderates the relationship, while board independence has a negative moderating effect. The government officials and policymakers can comprehend corporate tax avoidance behaviors of businesses and assist them in the formulation of suitable and efficient taxation policies.